An Analysis of Halal Assurance Practices as a Support for Sustainability in SME'S Bakery Production - Shalihin, Ahmad; Alda, Tania; Revadi, Chindy Elsanna; Nasution, Fadhylla Ramadani Putri (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: The purpose of this study is to analyze the consistency and suitability of the implementation of the Halal Product Assurance System (SJPH) in bakery MSMEs based on the Halal Product Assurance System (HAS) regulations in Indonesia, with an emphasis on environmental impacts and operational sustainability. Methodology: The research method used is qualitative descriptive observational. Results: The results of this study indicate that Rumah Roti UMKM has met 10 of the 11 criteria in the Halal Product Assurance System (SJPH), However, there is one criterion that has not been met, namely internal audit. Rumah Roti only conducts an internal audit once a year, which is considered insufficient to ensure compliance with halal standards and environmentally friendly practices consistently. Overall, although Rumah Roti has been quite good at implementing SJPH, improvements in internal audits are needed so that halal compliance and sustainability can be better maintained in the long term. Applications/Originality/Value: This study not only analyzes the implementation of the Halal Product Assurance System (HAS) in bakery MSMEs, but also emphasizes the environmental impact and operational sustainability. The focus on environmental aspects in halal certification is still rarely studied in the context of food MSMEs in Indonesia.